Evaluation of Staggered Osteotomy in Surgical Treatment of Trigonocephaly - Hassanpour, Seyed Esmail; Moosavizadeh, Seyed Mahdi; Hadi Sichani, Mohammad Reza; Alizadeh Otaghvar, Hamidreza; Tarahomi, Mohammadreza; Shojaei, Daryanaz; Molaei, Amir; Mohajerzadeh, Leili (Iranian Journal of Pediatric Surgery, 2017)
Introduction: undiagnosed metopic synostosis (Trigonocephaly) have many complications for infants such as Brain damage and cognitive & behavioral disorders, they also result in poor aesthetic features. There are many surgical techniques for this malformation which have their advantages and disadvantages; but with this new method (staggered osteotomy) we can solve some of these problems and minimize damages. Materials and Methods: In this study, 20 infants with metopic synostosis underwent surgery in Mofid Children Hospital, Tehran. The minimum age of our patients was 4 months and the maximum was 9 months with an average of 6.72 months. Their diagnosis was confirmed with clinical symptoms & signs also with CTscan and paraclinical findings. Age and weight before and after surgery and anthropometric indices including: biparietal width and frontal width were recorded and reported. Results: We found significant differences in anthropometric indices before & after surgery such as lowering of biparietal width after surgery and elevation of frontoparital index after surgery. Since in this procedure, we don’t separate the frontal bone segments and it keeps its frame, less plaques and screws are needed which will decrease the costs of surgery and the surgical time is much less than other techniques. Last but not the least, the satisfactions of parents were high and there was no need for secondary surgery. Conclusion:Based on all the perfect results we got , it is safe to say that staggered osteotomy as a surgical method for correction of trigonocephaly is useful and we can use it as a new method in correction of metopic synostosis.